EFEKTIVITAS MODEL PEMBELAJARAN SIMAYANG BERBASIS ETNOSAINS JAMU KUNYIT ASAM PADA MATERI ASAM BASA UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA - Pramesty, Niken Mega; Sunyono; Utami, Gamilla Nuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the effectiveness of the SiMaYang learning model, based on the ethoscience of turmeric and tamarind herbal medicine, in the context of acid-base conceptsto enhance students’ critical thinking skills. This study employed a quasi-experimental design with a pretest-posttest control group. The study population consists of 11th-grade students at State High School 16 Bandar Lampung for the 2026/2027 academic year. Sampling was conducted using cluster random sampling, resulting in Class XI.4 as the experimental class and Class XI.5 as the control class. The data analysis techniques in this study used a two-sample t-test and an effect size test.The results showed that the mean n-gain for critical thinking skills in the experimental classmet the “high” criterion, and there was a significant difference between the experimental and control classes. The effect size test yielded a value of 0.98, meeting the “large” criterion, indicating that 98% of the improvement in students’ critical thinking skills was attributed to the SiMaYang learning model based on the traditional medicine of turmeric and tamarind. Based on the results of the analysis conducted, it can be concluded that SiMaYang learning based on the ethoscience of turmeric and tamarind herbal medicine is effective in improving students’ critical thinking skills regarding acid-base concepts.